Advanced thermodynamics : fundamentals, mathematics, applications - Tabatabaian, Mehrzad; Rajput, R. K., 1944- (Mercury Learning & Information, 2018)
Designed for a course in thermodynamics or for use as a reference for practicing engineers, this book includes the theoretical underpinnings and derivations necessary for advanced study. -- Edited summary from book.
"Portions of this book appeared in Applied thermodynamics 2/E. Er R.K. Rajput"--Title page verso
Keywords: Thermodynamics -- Mathematics.; Thermodynamics.; Thermodynamics -- Industrial applications.; Thermodynamics -- Problems, exercises, etc.; elektronické knihy; electronic books